Effects of acetylsalicylic acid on germination, growth and chlorophyll amounts of cucumber (Cucumis sativus L.) seeds - Çanakci, Songül; Munzuro?lu, Ömer (Asian Network for Scientific Information, 2007)
Germination activities, various growth parameters (primary root length, hypocotyl length, primary leaf length, plant length and increase in fresh weight) and chlorophyll (a+b) amounts of cucumber seeds exposed to 0, 10 -5, 10-4, 10-3 and 0.5×10-2 M aqueous solutions of acetylsalicylic acid (ASA) for 48 h were established. While 0.5×10-2 M ASA significantly prevented germination activity of the seeds, other concentrations did not produce any effect, either positive or negative. Meanwhile, 0.5×10-2 M ASA inhibited radicle growth of the germinated seeds, while 10-5 M ASA increased radicle growth. Other concentrations of ASA did not affect radicle growth. The following findings were obtained from the one-week seedlings exposed to ASA for 48 h: 0.5×10-2 M ASA prevented growth (lengthening) of root, hypocotyl, leaf and plant and increased chlorophyll (a+b) amount with an increase in fresh weight. Contrary to 0.5×10-2 M ASA application, these features of the seedlings (except for the leaf length) were encouraged by 10-5 M ASA. 10-3 M ASA only prevented root growth and reduced chlorophyll (a+b) amount. Other concentrations of ASA did not bring about any positive or negative effect on the features studied. © 2007 Asian Network for Scientific Information.
Keywords: Acetylsalicylic acid; Chlorophyll; Cucumber; Germination; Growth